Follow-Up at 2 years After Emergency Surgery for Constrictive Pericarditis Complicated With Gastrointestinal Bleeding. (15th January 2022) - Zhao, Xu; Li, Chuntian; Zhong, Yue; Mao, Xin; Liu, Guiqing; Wang, Feng; Liang, Guiyou
Chronic constrictive pericarditis (CCP) is one of the common causes of cardiogenic cirrhosis; it is rare for a patient to have both CCP and recurrent black stool, so we consider that CCP causes cardiogenic cirrhosis. Cardiogenic cirrhosis caused portal hypertension which then resulted in gastrointestinal bleeding. Herein, we report a case of a 40-year-old Chinese woman suffering from CCP who had upper gastrointestinal bleed and had to undergo emergency surgery. Two years after the emergency surgery, multiple reexaminations showed significantly improved cardiac functions, hemoglobin, and WBC levels and gastrointestinal functions.